Analisis Statistik Konsumsi Energi Listrik pada Gedung Kantor Desa Pematang Johar Kecamatan Labuhan Deli Kabupaten Deli Serdang - Aulia Khairi; Pristisal Wibowo; Rahmaniar Rahmaniar (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2025)
Energy audit is a technique used to obtain the efficiency of a building with a certain method. Continuous research implementation is expected to be able to identify electrical efficiency and the purpose of data analysis is to obtain electrical energy efficiency to calculate the Energy Consumption Intensity (IKE) value in the building. Energy audits can also be carried out at any time or according to a predetermined schedule. Regular monitoring of energy usage is a must to find out the amount of energy used in each part of the operation during a certain period of time. Thus, savings efforts can be made.